Gut fermentation induced by a resistant starch rich whole grain diet explains serum concentration of dihydroferulic acid and hippuric acid in a model of ZDF rats. (February 2019) - Vitaglione, Paola; Mennella, Ilario; Ferracane, Rosalia; Goldsmith, Felicia; Guice, Justin; Page, Ryan; Raggio, Anne M.; Coulon, Diana; Martin, Roy; Keenan, Michael
Graphical abstract: Highlights: Resistant starch induces gut fermentation and modifies microbiota composition. Resistant starch rich whole grain increases serum total polyphenols. Gut fermentation explains dihydroferulic and hippuric acids serum concentrations. Abstract: This study aimed at assessing the influence of an 11 weeks intervention with a resistant starch-enriched whole grain diet (HI-RS-WG, 25% RS) compared to a WG control diet (LOW-RS-WG, 6.9% RS) on serum profile of polyphenols (PPs) in 20 Zucker Diabetic Fatty rats. Five PPs were identified and quantified in serum samples of rats belonging to both intervention groups. HI-RS-WG rats had 2.6 folds higher serum concentrations of total PPs than LOW-RS-WG rats. An explorative data reduction approach, based on the Principal Component Analysis identified two principal components related to the gut microbiota fermentation and food intake, respectively. Results showed that the abundance of hippuric acid and dihydroferulic acid in HI-RS-WG rats was explained by the stronger gut microbiota fermentation in those rats than in LOW-RS-WG rats.